Skarifikasi Awal Dan Penambahan Beberapa Jenis Zat Pengatur Tumbuh Untuk Percepatan Perkecambahan Benih Kayu Kuku (Pericopsis moonianna Thw) - Neneng Laila Romdyah; Melya Riniarti; Ceng Asmarahman; Slamet Budi Yuwono (Universitas Lambung Mangkurat, 2020)
Scarification was the destruction of the seed coat to softening seed coat and became permeable to water and gas. The purpose of this study was to obtain the best scarification techniques, types of growth regulatory substances and the combination of scarification treatments and addition of growth regulatory substances to accelerate the germination of Pericopsis mooniana seeds. The study was conducted using factorial randomized block design with three replications. The first factor was the scarification technique, with hot water, and broken the seed skin. The second factor was the addition of growth regulatory substances (coconut water and, bamboo shoots) shoot water and artificial growth regulatory substances Dates analyzed with variance and continued with the tukey test at 5% level. The results showed that the scarification technique by broken seed skin significant differences in the percentage of sprouts, germination, average days of germination, vigor index, number of leaves, and seedling height. The addition of growth regulatory substances did not show a significant difference in all observed variables.